2010
DOI: 10.1128/aac.00777-10
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Treatment-Naive Hepatitis C Virus (HCV) Clinical Isolates to HCV Protease Inhibitors

Abstract: In order to assess the natural variation in susceptibility to hepatitis C virus (HCV) NS3 protease inhibitors (PIs) among untreated HCV patient samples, the susceptibilities of 39 baseline clinical isolates were determined using a transient-replication assay on a panel of HCV PIs, including two ␣-ketoamides (VX-950 and SCH-503034) and three macrocyclic inhibitors (MK-7009, ITMN-191, and TMC-435350). Some natural variation in susceptibility to all HCV PIs tested was observed among the baseline clinical isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 31 publications
3
51
2
Order By: Relevance
“…The V55A mutation confers low resistance to boceprevir (47). The Q80K mutation is associated with significantly reduced susceptibility to TMC-434350 and low-level resistance to vaniprevir and danoprevir but wild-type susceptibility to telaprevir and boceprevir (3). The other mutations associated with resistance were observed only as low-level variants, and most of them were detected in one clone per sample; only mutations Q41R and D168G were found in two clones of the same sample.…”
Section: Discussionmentioning
confidence: 92%
“…The V55A mutation confers low resistance to boceprevir (47). The Q80K mutation is associated with significantly reduced susceptibility to TMC-434350 and low-level resistance to vaniprevir and danoprevir but wild-type susceptibility to telaprevir and boceprevir (3). The other mutations associated with resistance were observed only as low-level variants, and most of them were detected in one clone per sample; only mutations Q41R and D168G were found in two clones of the same sample.…”
Section: Discussionmentioning
confidence: 92%
“…The sequence analysis for NS3 protease of genotype 1a in patients who received the simeprevir regimens detected a relevant polymorphism Q80K in 19-48% [13]. In vitro studies showed that this mutation decreases viral response to simeprevir by 10folds [13]. Less profound inhibition has been observed in other NS3 inhibitors including sovaprevir and asunaprevir.…”
Section: Ns3/ns4a Protease Inhibitorsmentioning
confidence: 99%
“…The low genetic barrier for developing resistance in the second-generation protease inhibitors is still the major obstacle facing their activities. The sequence analysis for NS3 protease of genotype 1a in patients who received the simeprevir regimens detected a relevant polymorphism Q80K in 19-48% [13]. In vitro studies showed that this mutation decreases viral response to simeprevir by 10folds [13].…”
Section: Ns3/ns4a Protease Inhibitorsmentioning
confidence: 99%
“…For instance, variations in NS3-V170 are present in most HCV genotype 1 isolates, and polymorphism in NS3-D168 is characteristic of HCV genotype 3 [32] . As the development of NS3/4A PIs was based in HCV genotype 1, subtype 1b, their antiviral activity with non-1b genotypes, may be not as effective, although some PIs inhibit more than one HCV genotype [22,42,[48][49][50] . Currently neither Boceprevir nor Telaprevir should be used in patients infected with HCV genotypes other than 1.…”
Section: Hcv Resistance To Ns3/4a Pismentioning
confidence: 99%
“…In fact, resistant variants arise from preexisting subpopulations of viral genomes already circulating in the infected individual, before therapy is started [19] . Selective drug pressure changes the balance between the different intra-individual HCV quasispecies; and resistant genomes dominate the circulating viruses in patients with treatment failure or suboptimal treatment response, as evidenced in patients treated with NS3/4 PIs [20][21][22] . Fortunately, resistant variants remain sensitive to Peg-IFN + RBV, which still makes their elimination possible with the current Peg-IFN + RBV treatment [16] .…”
Section: Introductionmentioning
confidence: 99%